Relationships Between Dye Reduction Test Scores and Somatic Cell Count in Bovine Raw Milk - Baris Kadir Yalcin; Savas Atasever (Turkish Journal of Agriculture: Food Science and Technology, 2018)
The aim of this study was to reveal the relationships between dye reduction test scores and somatic cell count (SCC) in bovine raw milk. The SCC, methyelene blue reduction scores (MTS) and resazurin reduction test scores (RTS) were determined at biweekly intervals in four test days (TD) between March and April 2017 in a total of 89 raw milk samples sold in Samsun province as unpacked. While SCC values were recorded by an automatic counter, all SCC values were transformed to log10 base before statistical analysis. In MTS method, the time for the change of the color of milk from blue to white was noted and milk quality was assessed using a 1 to 4 point scale (1=>5h-good/excellent; 2=2-5h-medium; 3=0.5-2h-bad and 4=